In Vivo Neuronal Cell Differentiation Imaging From Transplanted Stem Cells - Soo Lee, Dong (Current Medical Imaging, 2012)
In vivo cell tracking has been enabled by molecular imaging technology and, recently, monitoring cell fate changes has become possible in small animals. Stem cells and induced pluripotent stem cells (iPSCs) can differentiate in vivo after implantation, and lineage commitment of these cells can be successfully imaged using cell-specific promoterdriven reporter genes. For this purpose, imaging sensitivity has been significantly enhanced by engineering luciferase or adopting molecular amplification techniques. After transplantation of stem cells within a polymer scaffold, the fate changes of cells into neuronal lineages were monitored long enough to recognize possible adoption within endogenous microenvironment. Multiplexing and optimizing the imaging method to trace fate changes of transplanted stem cells can now be implemented broadly in vivo in small animals and possibly in humans.
Keywords: Optical imaging